Community-acquired pneumonia as a common acute infectious disease of the respiratory system - A. A. Wiesel; I. Y. Wiesel; G. V. Lysenko (Медицинский совет, 2014)
The article is an overview of studies on morbidity and mortality from community-acquired pneumonia worldwide. There is data on the Republic of Tatarstan over the last two decades